An Analysis of the Single Tuition Fee System at Medan State University - Siregar, Theresia Febriana; Sitompul, Farid Hakim; Simbolon, Stiven Solomo; Istiqomah; Simanihuruk, Christina (META: Journal of Science and Technological Education, 2024)
The Single Tuition Fee (UKT) system at Universitas Negeri Medan (Unimed) reflects a commendable initiative to promote equitable access to higher education by tailoring tuition fees to students' economic capacities. This study examines the implementation and impact of the UKT system in 2024, with a focus on its distribution across socioeconomic groups and students' perceptions of university services. Data collection involved a Google Form survey and interviews with students from various faculties, analyzed using descriptive statistical methods. The findings highlight a concentration of students in lower-income UKT brackets, aligning with the system's inclusivity goals. However, opportunities for enhancement were identified, particularly regarding transparency in the UKT allocation process and the alignment of university services with students' expectations. This study underscores the importance of refining the system to foster fairness and satisfaction while maintaining Unimed’s commitment to accessible and high-quality education for all.